A Comprehensive Understanding of Vocational Students' Engagement in The Merdeka Curriculum: A Preliminary Study - Sa'adah, Halimatus; Indah, Rohmani Nur; Afifi, Nur (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This research presents a comprehensive understanding of how Vocational High School students are engaged and explores the various factors that affect student engagement in the implementation of the Merdeka Curriculum. It aims to examine the implementation of Merdeka Curriculum on student engagement at Vocational High School in optimizing student abilities through practical learning. In collecting and analyzing data, this research used Systematic Literature Review (SLR) to identify relevant literature through databases and was determined based on predetermined criteria. The results showed that student engagement is determined by teachers' understanding of the Merdeka Curriculums’ concept which affects the learning strategies used to design the learning process. In addition, the flexibility and freedom in the concept of implementing a Merdeka Curriculum given to teachers is another factor to support student participation during the learning process. Therefore, it is concluded that student engagement is determined by how the teacher is able to implement the independent curriculum properly. This research suggested that optimizing student engagement can be done through the design of learning process adjusted to the needs and interests of students based on their vocations.